2018
DOI: 10.1148/radiol.2017170517
|View full text |Cite
|
Sign up to set email alerts
|

Screening Digital Mammography Recall Rate: Does It Change with Digital Breast Tomosynthesis Experience?

Abstract: Purpose To compare screening mammography recall rate, cancer detection rate (CDR), and positive predictive values (PPVs) for digital mammography before and after radiologist experience with digital breast tomosynthesis (DBT). Materials and Methods This retrospective study was approved by the institutional review board and compliant with HIPAA. The authors reviewed screening mammography audit data obtained from 2009 to 2014, during which 108 276 digital mammographic examinations were performed (50 062 before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…With the supplemental screening modalities, the performance of screening may be influenced. For example, one study showed an average recall rate of 7.9% (range from 5.5% to 9.5%) after applying DBT and 6.8% (range from 3.6% to 9.7%) before DBT ( p = 0.0316) [ 31 ]. Compared to the current study, the recall rate after DBT is similar to that of our overall value; however, it is higher than that of our follow-up visit group.…”
Section: Discussionmentioning
confidence: 99%
“…With the supplemental screening modalities, the performance of screening may be influenced. For example, one study showed an average recall rate of 7.9% (range from 5.5% to 9.5%) after applying DBT and 6.8% (range from 3.6% to 9.7%) before DBT ( p = 0.0316) [ 31 ]. Compared to the current study, the recall rate after DBT is similar to that of our overall value; however, it is higher than that of our follow-up visit group.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only 1 study examining DM performance after DBT experience, which reported increased recall and cancer detection rates for DM after vs before DBT use in a single practice . Notably, the 6 radiologists in that study had very low DM recall rates (mean, 6.8%) and very low cancer detection rates (mean, 2.5 per 1000 examinations) before DBT use.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, there is scant information on the effect of comparison DM/DBT on DM interpretation. DiPrete et al reported performance metrics in two DM cohorts, before and after DM/DBT implementation, 23 demonstrating increases in recall rate, cancer detection rate, and PPV 2,3 in the post‐DM/DBT cohort. It is quite possible that the nature of the comparison examination may be a driver of performance metrics for which we have not accounted.…”
Section: Discussionmentioning
confidence: 99%